To Wait or Not to Wait—Separate Mechanisms in the Oculomotor Circuit of Basal Ganglia - Yasuda, Masaharu; Hikosaka, Okihide (Frontiers in Neuroanatomy, 2017)
We reach a goal immediately after detecting the target, or later by withholding the immediate action. Each time, we choose one of these actions by suppressing the other. How does the brain control these antagonistic actions? We hypothesized that the output of basal ganglia, substantia nigra pars reticulata (SNr), suppresses antagonistic oculomotor signals by sending strong inhibitory output to superior colliculus (SC). To test this hypothesis, we trained monkeys to perform two kinds of saccade task: Immediate (visually guided) and delayed (visually-withheld but memory-guided) saccade tasks. In both tasks, we applied one-direction-reward (1DR) procedure to modify the level of goal-reaching motivation. We identified SNr neurons that projected to SC by their antidromic activation from SC. We stimulated SC on both sides because SNr neurons projecting to the ipsilateral SC (ipsiSC) and those projecting to the contralateral SC (contraSC) might have antagonistic functions. First, we found that ipsiSC-projecting neurons were about ten times more than contraSC-projecting neurons. More importantly, ipsiSC-projecting SNr neurons were roughly divided into two groups which would control immediate and delayed saccades separately. The immediate-type SNr neurons were clearly inhibited by a visual target on the contralateral side in both visual- and memory-1DR tasks. The inhibition would disinhibit SC neurons and facilitate a saccade to the contralateral target. This is goal-directed in visual-1DR task, but is erroneous in memory-1DR task. In contrast, the delayed-type SNr neurons tended to be excited by a visual target (especially on the contralateral side), which would suppress the immediate saccade to the target. Instead, they were inhibited before a delayed (memory-guided) saccade directed to the contralateral side, which would facilitate the saccade. ContraSC-projecting SNr neurons were more variable with no grouped features, although some of them may contribute to the saccade to the ipsilateral target. Finally, we found that some ipsiSC-projecting SNr neurons were inhibited more strongly when reward was expected, which was associated with shortened saccade reaction times. However, many SNr neurons showed no reward-expectation effect. These results suggest that two separate oculomotor circuits exist in basal ganglia, both of which contribute to goal-directed behavior, but in different temporal contexts.